Training undergraduate research assistants with an outcome‐oriented and skill‐based mentoring strategy. Issue 8 (15th July 2022) - Della Corte, Dennis; Morris, Connor J.; Billings, Wendy M.; Stern, Jacob; Jarrett, Austin J.; Hedelius, Bryce; Bennion, Adam
Abstract : It is found that research mentoring of undergraduate students can result in meaningful contributions to scientific disciplines. Here, an outcome‐oriented, skill‐based mentoring strategy is proposed and evaluated in the context of the CASP14 community challenge. Abstract : Effective mentoring of undergraduate students is a growing requirement for the promotion of faculty at many universities. It is often challenging for young investigators to define a successful mentoring strategy, partially due to the absence of a broadly accepted definition of what mentoring should entail. To overcome this, an outcome‐oriented mentoring framework was developed and used with more than 25 students over three years. It was found that a systematic mentoring approach can help students quickly realize their scientific potential and result in meaningful contributions to science. This report especially shows how the Critical Assessment of Protein Structure Prediction (CASP14) challenge was used to amplify student research efforts. As a result of this challenge, multiple publications, presentations and scholarships were awarded to the participating students. The mentoring framework continues to see much success in allowing undergraduate students, including students from underrepresented groups, to foster scientific talent and make meaningful contributions to the scientific community.